Atlas of Neoplastic Pulmonary Disease Pathology, Cytology, Endoscopy and Radiology - Fraire, Armando E.; Cagle, Philip T.; Irwin, Richard S.; Mody, Dina R.; Ernst, Armin.; Blackmon, Shanda.; Allen, Timothy Craig.; Dishop, Megan K. (Springer US, 2010)
Atlas of Neoplastic Pulmonary Disease: Pathology, Cytology, Endoscopy and Radiology is a unique atlas that provides images from four major disciplines involved in the study and diagnosis of lung tumors. This atlas, containing 41 chapters represents a wide range of neoplastic lung entities and will be a quick and reliable interdisciplinary tool for the practitioner involved in the management of lung tumors.